Creativity Education Model through Dance Creation for Students of Junior High School - Malarsih, M.; Herlinah, H. (Department of Drama, Dance, and Musik (Sendratasik), Semarang State University, 2014)
This study aims to realize dance as a real product of a dance education process. The product is packaged in a form of audio-visual as well as a scientific publication. As the benefit from this study, the product can be used by school and specifically by dance teacher as a guidance in conducting dance lesson at school. The study on the model of creativity education through the creation is being understood as a form of developmental research. As a developmental research, the research plan is initiated by analyzing the teaching material related to dance lesson, and relate it to the creativity education which has to be accomplished through dance lesson, specifically for Junior High School students. The study will be continued with theoretical/ conceptual analysis and observation which is related to creativity education through the dance creation. In the end of this study, model of creativity education through dance creation is produced, particularly for students of Junior High School level. Results of the study show that, in doing creativity activity through dance creation, the value of the dance as an art is not become the primary aim. Moreover, the main aim of this process is towards the creativity process itself. While producing and creating the dance, two major educational points are derived, which are: the creativity and product value in a form of dance. Based on background of the idea, through this pilot project, the creativity of creating dance for public schools students, especially Junior High School, is possible to be done and used as a dance creativity learning model in Junior High School. Two suggestions are formulated in this study: (1) it is suggested for dance teachers in public schools, in this context is Junior High School teachers, to set their teaching and learning process into the creativity education as it is implied in curriculum. (2) In order to achieve the creativity education itself, the dance creation as one of art subject which is given to schools, should become the main priority in its learning implementation as an instrument to build students character to be more creative in thinking.